Lipopolymer Nanoparticle‐Mediated In Vivo CRISPR‐Cas9 Editing of Mrg15 Restores Mitochondrial Mitophagy to Alleviate Metabolic‐Associated Steatohepatitis - Zixi Zhang; Jing Liao; Tingfeng Yu; Sijie Chen; Ling Zeng; Guanzi Chen; Qian Shen; Yingsen Tang; Meng Jiang; Jinjin Chen; Lingyun Wang (Advanced Healthcare Materials, 2026)
ABSTRACT Metabolic‐associated steatohepatitis (MASH) remains difficult to treat due to the lack of interventions capable of targeting upstream disease drivers and achieving durable disease modification. The epigenetic regulator Mrg15 has been implicated in mitochondrial dysfunction and metabolic stress in the liver, suggesting its potential relevance to MASH pathogenesis. Here, we develop a liver‐targeted lipopolymer nanoparticle (LPNP)‐mediated gene editing platform to enable in vivo disruption of Mrg15 by co‐delivery of Cas9 mRNA and Mrg15 sgRNA. The screened P64H/Mrg15 system achieved efficient hepatic delivery and genome editing, resulting in reduced Mrg15 expression in hepatocytes. In the MASH mouse model, P64H/Mrg15 treatment was associated with decreased hepatic lipid accumulation, improved liver injury markers, and attenuation of inflammation and fibrosis. Sequence‐level analyses confirmed on‐target editing in liver tissue, and systemic histopathological evaluation revealed no overt toxicity in major organs under the tested dosing regimen. Transcriptomic profiling revealed coordinated pathway‐level associations involving metabolic, inflammatory, and autophagy‐related regulation, while protein‐level analyses demonstrated alterations in selected autophagy‐ and mitophagy‐related regulators, including TUFM and LC3B‐II. Together, these findings identify Mrg15 as a disease‐relevant epigenetic regulator in MASH and highlight liver‐directed P64H LPNP/CRISPR delivery as a promising non‐viral strategy for modulating upstream regulatory pathways in metabolic liver disease.